Inter-generation culture of academic members in Iran with emphasis on local features - Z. Mohammadi (Taḥqīqāt-i Farhangī-i Īrān)
University is as a socio-cultural place in which generational relations flow intergenerational and within a same generation and it has effects on specialized services. The purpose of this research is to study the generations of Iranian academics and compare them with generations in the world to study the social characteristics of each generation in their ecosystems. The research method is documentary and analytical reasoning. In the theoretical discussions, there are five generations of Iranians corresponding to the five generations of the contemporary world; First generation: veterans/ Iranian constitutional generation; Second generation: Boomers/ the generation of Iranian nationalism; Third generation: generation X/ generation of modernization in Iran; Fourth generation: generation Y or Millennium/ Generation of Islamic Revolution; Fifth generation: Z or Net generation/ Generation of Post-Revolution. The first generation is familiar with the Mertonian norms and tradition of staying in an elite university. The second generation is accompanied by the growth of political norms and dominant scientific norms. The third generation is associated with the growth of politics and ideology along with learning science and then its conquest. In the fourth generation, growth has started, and the turn is from education to research and science two style sciences. In the fifth generation, knowledge has been a commodity and business, the rotation is from research to entrepreneurship along with a decline in the tradition of residence. The result is that the serious differences in the characteristics of the fifth generation in the last century have caused these different generations not be able to experience creative and effective academic lives.